Tree Species Composition and Distribution in Ayer Hitam Forest Reserve, Puchong, Selangor - Lepun, Philip (2002)
The study was conducted in Ayer Hitam Forest Reserve (AHFR), Puchong, Selangor to assess the floristic composition, stand attributes (including basal area, stem density, volume, above-ground biomass) and the tree species distribution. Besides that, the study aims to recognize the conservation status of tree species, potential increment of the species within the sampling area and it regenerating level by using the summation method. The enumeration of trees >5 cm dbh in the 5-ha plot recorded 6,621 trees which belong to 50 families, 148 genera and 319 species. Euphorbiaceae in this plot was found dominant in genera and tree stems but Myristicaceae has the most number of species with 27 species. Agrostistachys longifolia var. longifolia recorded 7.0% of all trees was the highest in stem number. Shannon-Weiner diversity i ndex, H' of the area was calculated at 4.74. I n this study, 4.4% of the endemic species for Peninsular Malaysia and 9.4% of the tree species was recorded for the first time for the state of Selangor. Only Artocarpus lowii was identified as uncommon and Canarium sumatranum is a rare species occurring in this area. Ayer Hitam Forest Reserve stratification and the stand density could be divided into five classes. The secondary species found occurring in this plot was 4.1% of the tree species. The total basal area, volume and aboveground biomass of the trees in 5-ha plot was 161.7 m2, 6,316.5 m3 and 1,777.2 t respectively. Every addition of a hectare in the contiguous area in t h e AHFR shows that there is an increase accumulative num ber o f species with the ranges of 9-35 species.